On the Interpretation of Individual Variables in Multiple Discriminant Analysis - Karson, Marvin J.; Martell, Terrence F. (Journal of Financial and Quantitative Analysis, 1980)
Marvin J. Karson, Terrence F. Martell, On the Interpretation of Individual Variables in Multiple Discriminant Analysis, The Journal of Financial and Quantitative Analysis, Vol. 15, No. 1 (Mar., 1980), pp. 211-217